PENINGKATAN PEMAHAMAN SISWA DALAM MEMAHAMI PETA DENGAN METODE DISKUSI PADA SISWA IV SDN 192 BARRU - Mutiara; Haslinda; Syahrul Pratama (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to enhance students' understanding of maps through the implementation of discussion methods among fourth-grade students at SDN 192 Barru. It explores the significance of map comprehension in geography education and underscores the role of discussion methods as an effective approach to improving students' grasp of map concepts. Maps, as essential tools for understanding space, location, and spatial relationships, hold a central position in geographic learning. However, the challenge of interpreting the information presented in maps often serves as a barrier to students achieving optimal comprehension. This article delves into how the application of discussion methods can aid students in overcoming these challenges through active interaction, exchanging ideas, and collaboratively exploring map concepts. By engaging in discussions, students can clarify misunderstandings, enhance critical thinking, and build deeper connections with the subject matter. The findings of this research provide valuable insights for educators, emphasizing the importance of fostering an interactive and student-centered learning environment to improve spatial literacy. This approach not only addresses the difficulties faced by students in interpreting maps but also cultivates their ability to analyze spatial data effectively. The study offers a framework for teachers to develop innovative teaching strategies that prioritize collaboration and active participation, ultimately contributing to more meaningful and effective geography education.